2005
DOI: 10.1016/j.heares.2005.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the precedence effect in auditory evoked potentials

Abstract: The precedence effect in subjective localization tasks reflects the dominance of directional information of a direct sound (lead) over the information provided by one or several reflections (lags) for short delays. By collecting data of both psychoacoustical measurements and auditory evoked potentials the current study aims at neurophysiological correlates for the precedence effect in humans. In order to investigate whether the stimulus features or the perception of the stimulus is reflected on the ascending s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 35 publications
11
22
0
Order By: Relevance
“…First, amplitudes of auditory brainstem responses evoked by sequences of two impulses showed responses to the second to be unaffected by the first once the temporal separation exceeded 4-5 ms (Damaschke et al, 2005;Bianchi et al, 2013). This 5-ms window is consistent with computational modeling work of Xia et al (2010): simulated medial superior olive responses to lagging pulses at a cell's best ITD are unaffected by preceding pulses for echo delays longer than 5 ms. Because of these findings, there will be no effort in the current paper to model effects by considering cochlear interactions between leading and lagging pulses a la Hartung and Trahiotis (2001).…”
Section: Introductionsupporting
confidence: 79%
“…First, amplitudes of auditory brainstem responses evoked by sequences of two impulses showed responses to the second to be unaffected by the first once the temporal separation exceeded 4-5 ms (Damaschke et al, 2005;Bianchi et al, 2013). This 5-ms window is consistent with computational modeling work of Xia et al (2010): simulated medial superior olive responses to lagging pulses at a cell's best ITD are unaffected by preceding pulses for echo delays longer than 5 ms. Because of these findings, there will be no effort in the current paper to model effects by considering cochlear interactions between leading and lagging pulses a la Hartung and Trahiotis (2001).…”
Section: Introductionsupporting
confidence: 79%
“…High-level, cognitive processes might also influence the precedence effect (Blauert et al, 1989;Clifton et al, 1994;Mccall et al, 1998;Freyman et al, 1991;Damaschke et al, 2005). These studies suggest that echo processing may depend on the listeners' prior listening experience and the resulting expectations about the sound-source position and the room acoustics.…”
Section: Discussionmentioning
confidence: 89%
“…This positive peak (Pa) was reduced in amplitude when a sound was presented as a simulated reflection rather than in isolation. A second study reported psychophysical, ABR, and ERP measurements and concluded that the earliest evidence of the precedence effect in the ERP waveforms was the mismatch negativity (MMN) which peaked around 150 ms after the onset of the lag sound (Damaschke et al, 2005). However, neither of these studies recorded participant responses during or under precisely the same conditions as electrophysiological measurements.…”
Section: Introductionmentioning
confidence: 99%